The technology of extraction and enrichment of scandium from uranium-phosphorus-rare earth concentrate - Mukhachev, A.P.; Yelatontsev, D.O.; Kharitonova, O.A. (Problems of Atomic Science and Technology, 2023)
The paper presents the results of pilot tests of scandium extraction technology from uranium-rare-earth phosphorite to obtain high-purity scandium oxide Sc₂O₃. It is shown that scandium in phosphorites is accompanied by thorium and rare earth elements (REE), which requires the development of a technology for the complex processing of raw materials. Scandium with a purity of 99.0% was obtained from a concentrate of various degrees of enrichment and shavings of scandium alloys by dissolving them in sulfuric acid, extraction, and selective precipitation with oxalic acid. In the process of testing, scandium oxides were obtained with a purity of 99.0; 99.9, and 99.99%, suitable, for example, for the production of alloys based on magnesium for medical purposes. Викладено результати дослідно-промислових випробувань технології вилучення скандію з уран-рідкісно-земельного фосфориту з отриманням високочистого оксиду скандію. Показано, що у фосфоритах скандію супроводжують торій та рідкісно-земельні елементи (РЗЕ), що потребує розробки технології комплексної переробки сировини. Скандій чистотою 99,0% отримували з концентрату різного ступеня збагачення та стружки сплавів скандію методами розчинення їх в азотній кислоті, екстракції та селективного осадження щавлевою кислотою. В процесі випробувань були отримані оксиди скандію Sc₂O₃ чистотою 99,0, 99,9 і 99,99%, придатні для отримання сплавів на основі магнію медичного призначення.